Alone in a Crowd: Social Isolation, Place, and Connection in Later Life - Weldrick, Rachel (My University, 2021)
The problem of social isolation among older people has been thoroughly documented, studied, and addressed through both policy and social services, and yet persists as a major social issue. There exist several notable gaps within the scholarly literature on isolation, particularly with respect to the role(s) of place-based risk factors, the relationship(s) between exclusion and social isolation, and best practices for isolation interventions. This thesis addresses these knowledge gaps and presents both empirical and theoretical contributions resulting from a three-part investigation. These studies are presented in three distinct papers to constitute a sandwich dissertation. The first paper examines the role of neighbourhood characteristics in shaping social isolation among older people by analyzing the Canadian Longitudinal Study on Aging (CLSA) baseline data in a series of multiple regressions. Findings indicate that the selected neighbourhood characteristics account for only a small portion of the social outcome measures of interest but raise meaningful questions about the intersection of place and social connection that warrant further study. The second paper investigates both the harmful and protective aspects of places in shaping isolation risk through a qualitative study of older people informed by a place-based exclusion lens. Interview results highlight several aspects of places that contribute risk of isolation and are used to adapt the model of known isolation risk factors. The third and final paper analyzes a sample of friendly visiting programs by conducting a realist synthesis to determine how, for whom, and under what conditions friendly visiting programs are most successful. Results of the synthesis are used to build a friendly visiting program theory to be tested in future studies. Together these three papers contribute to both the applied and theoretical literature on social isolation, and can inform the development of future research, policy, and intervention strategies.
Keywords: gerontology; aging; social isolation; living alone